The urokinase receptor (CD87) facilitates CD11b/CD18-mediated adhesion of human monocytes. - Sitrin, R G (1996)
Urokinase receptors (uPAR; CD87) from complexes with complement receptor 3 (CR3) (CD11b/CD18), a beta2 integrin. In this study, we sought to determine if this association modulates the adhesive function of CR3. Both CR3 and uPAR concentrate at the ventral surface of fibrinogen-adherent human monocytes, and CR3-uPAR coupling increases substantially upon adhesion to fibrinogen. Pretreatment with anti-uPAR monoclonal antibody reduced adhesion to CR3 counterligands (fibrinogen and keyhole limpet hemocyanin) by 50%, but did not affect adhesion to fibronectin, a beta1 integrin counterligand. Antisense (AS) oligonucleotides were used to determine if selectively suppressing uPAR expression also modulates CR3 adhesive function. AS-uPAR oligo reduced CR3-dependent adhesion by 43+/-9% (P<0.01), but did not affect CR3-independent adhesion. To determine if the effects of uPAR are mediated through its ligand, monocytes were pre-treated with AS oligo to block uPA expression. Unlike the effects of blocking uPAR expression, AS-uPA oligo increased adhesion by 46% (P<0.005), and exogenous intact uPA, but not uPA fragments, reversed this effect. We conclude that complex formation with uPAR facilitates the adhesive functions of CR3. This function of uPAR is not dependent upon its occupancy with uPA, which negatively influences adhesion.